Ovipositional responses of Spodoptera frugiperda on host plants provide a basis for using Bt-transgenic maize as trap crop in China - Li-mei HE; Sheng-yuan ZHAO; Xi-wu GAO; Kong-ming WU (Journal of Integrative Agriculture)
Spodoptera frugiperda, the pest fall armyworm (FAW), is widespread in more than 100 countries. To date, planting insect-resistant transgenic crops is one of the main control methods in its native countries. In this study we evaluated Bt-transgenic maize (Bt maize) and non-transgenic (conventional) maize and six other host plants in greenhouse pot experiments and field trials for oviposition preference by the Chinese populations of FAW. In laboratory trials, female moths preferred to oviposit on maize with no significant preference between conventional and Bt maize. However, after conventional and transgenic maize were exposed to FAW larvae and damaged, oviposition was significantly higher on transgenic maize than on the conventional one. Field trials showed that for plants less damaged at an early stage (seedling stage), oviposition of FAW on transgenic and conventional maize was significantly higher than that on wheat, sorghum, foxtail millet, peanut and soybean while showing no significant difference between transgenic or conventional maize. FAW adults mainly laid eggs on Bt maize, while the larval density and leaf damage rating or percentage of damaged plants were significantly lower than on conventional maize. Larval density and its damage on conventional maize were significantly higher than that on Bt maize and the other five hosts. Thus, maize is a highly preferred and suitable host for S. frugiperda feeding and ovipositing, and Bt maize can be used as trap crop to protect other crops.